Signifikansi Nalar Ijtihad Al-Jâbirî Terhadap Pemaknaan Ulang Konsep Jihad Era Kontemporer - Abid Rohmanu (Ulumuna, 2006)
Nowadays, in the modern era, we can obviously witness some groups of moslems still commit some terrors action to other religion and/or to out-group-moslems just because of different understanding of Islamic dogma. These radical groups of moslem claim that their actions are on behalf of religious’ belief. But, since the very beginning of revelation, Islam ask its followers to spread peace, harmony and prosperity among human being, as Islam have essential principle “rahmah li al-‘alamin”. So, certain perspectives or ways of understanding Islamic teaching applied by those groups are assumed to have emerged their negative response to other religion and out-group-moslems. This paper examines the significance of rational understanding to Islam proposed by al-Jâbirî to reinterpretation of jihad in the modern context. The point of al-Jâbirî’s rational view is relevant factor to eliminate and minimize normative understanding to Islam.